Developmental and genetic perspectives on Pierre Robin sequence. Issue 4 (11th October 2013) - Tan, Tiong Yang; Kilpatrick, Nicky; Farlie, Peter G.; Cox, Timothy C.; Luquetti, Daniela V.; Cunningham, Michael L.
Abstract Pierre Robin sequence (PRS) is a craniofacial anomaly comprising mandibular hypoplasia, cleft secondary palate and glossoptosis leading to life‐threatening obstructive apnea and feeding difficulties during the neonatal period. The respiratory issues require careful management and in severe cases may require extended stays in neonatal intensive care units and surgical intervention such as lengthening the lower jaw or tracheotomy to relieve airway obstruction. These feeding and respiratory complications frequently continue well into childhood, affecting not only growth and development but also impacting on long term educational attainment. The diagnosis of PRS depends on readily recognizable clinical features but the phenotypic similarity of many PRS individuals conceals considerable etiological heterogeneity. Defects in the growth of the mandible sit at the core of PRS and the natural history of PRS can be classified into two major streams: primary defects of mandibular outgrowth and elongation and issues that are external to the mandibular skeleton but that secondarily impact on its growth. These altered developmental trajectories appear to be driven by a range of influences including defects in cartilage growth, neuromuscular function and fetal constraint. Various genetic and cytogenetic associations have been made with PRS and the diversity of these associations highlights the fact that there are numerous ways to arrive at this common phenotypic endpoint. © 2013 Wiley Periodicals, Inc.